TRENDS IN MODERN WOMEN'S RELATIONS IN SOCIAL PROBLEMS: Islamic Law in Tafsir Al-Qurtubi - Ida Syarifah, Zulfi; Ulinnuha, Muhammad; Al Munawar, Said Agil Husin; Muhammad, Habli Husna (Al-Risalah, 2025)
This study aims to analyze modern women’s relationships and the accompanying social problems from an Islamic legal perspective, using Imam al-Qurtubi’s Tafsir al-Jami’ li Ahkam al-Qur’an as the primary reference. This research gap lies in the limited number of studies directly linking classical fiqh interpretations to contemporary women’s socio-legal problems through contextual and socio-legal approaches. This study employed a qualitative approach using interpretive analysis and normative-contextual studies. Data were collected through a literature review of Tafsir al-Qurtubi, fiqh books, and academic studies on Islamic law and gender, supplemented with empirical social data from official sources and social observations of modern women’s relationships. The analysis techniques used are textual analysis, historical-contextual analysis, and a comparative analysis of the normative construction of the interpretation and contemporary social reality. The results of this study indicate that although the Tafsir Al-Qurtubi was born in a medieval patriarchal social context, it consistently positions women as equal legal and moral subjects. Key concepts such as qiwamah (the act of worship), honor, and women’s public role are interpreted as responsibilities and protections rather than as the basis for the legitimacy of domination. In this context, Tafsir Al-Qurtubi is a relevant normative basis for formulating just, inclusive, and welfare-oriented legal solutions for modern women.